2013
DOI: 10.1016/j.jbiomech.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of gastrocnemius muscles forces in walking and running goats predicted by one-element and two-element Hill-type models

Abstract: Hill-type models are commonly used to estimate muscle forces during human and animal movement —yet the accuracy of the forces estimated during walking, running, and other tasks remains largely unknown. Further, most Hill-type models assume a single contractile element, despite evidence that faster and slower motor units, which have different activation-deactivation dynamics, may be independently or collectively excited. This study evaluated a novel, two-element Hill-type model with “differential” activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 25 publications
4
62
1
Order By: Relevance
“…For the Hill model, the level of agreement between predicted and experimental data is not perfect, which is in line with previous work (Lee et al, 2013;Krylow and Sandercock, 1997;Williams et al, 1998;Sandercock and Heckman, 1997). This suggests that caution is necessary when applying the model in situations in which accurate quantification of muscle force is required (e.g.…”
Section: Hill and Huxley Mtc Models Yield Similar Predictions Of Expesupporting
confidence: 82%
See 3 more Smart Citations
“…For the Hill model, the level of agreement between predicted and experimental data is not perfect, which is in line with previous work (Lee et al, 2013;Krylow and Sandercock, 1997;Williams et al, 1998;Sandercock and Heckman, 1997). This suggests that caution is necessary when applying the model in situations in which accurate quantification of muscle force is required (e.g.…”
Section: Hill and Huxley Mtc Models Yield Similar Predictions Of Expesupporting
confidence: 82%
“…potentiation (Krarup, 1981) and shorteninginduced force depression (Meijer et al, 1997;Rassier and Herzog, 2004)]. With respect to the first option, Lee et al (2013) have recently shown that explicit modelling of fibre type distribution can improve Hill model predictions of goat m. gastrocnemius mechanical behaviour in vivo. However, rat SOL consists for the most part of slow-twitch, type I fibres (∼85%, Delp and Duan, 1996;Pousson et al, 1991).…”
Section: Hill and Huxley Mtc Models Yield Similar Predictions Of Expementioning
confidence: 99%
See 2 more Smart Citations
“…However, at low motor unit firing rates, differences in the predicted and measured forces were greater than 50% (Perreault et al, 2003). Our own efforts to predict in situ and in vivo forces generated by the gastrocnemius muscles of goats (Wakeling et al, 2012;Lee et al, 2013) confirmed that Hill-type models are sensitive to assumptions about activation state and the force-velocity properties of the model's contractile element. For example, we have shown that Hill-type models reproduce the timevarying in vivo forces with an average r 2 of 0.40, and errors in force greater than 15% and 28% of maximum isometric force for the medial (MG) and lateral (LG) gastrocnemii of goats, respectively, when averaged across the gait cycle and different locomotor speeds.…”
Section: Introductionmentioning
confidence: 52%